1997
DOI: 10.1007/s004380050516
|View full text |Cite
|
Sign up to set email alerts
|

Use of allele specificity of comigrating AFLP markers to align genetic maps from different potato genotypes

Abstract: The allele specificity of AFLP markers was assessed in five relatively unrelated potato genotypes. To this end, two diploid mapping populations of potato, F1SH x RH and F1AM x RH, were analysed using four and six AFLP primer combinations, respectively, recently applied to the analysis of the genetically well characterized backcross population BC_C x E. The AFLP profiles of the five parents revealed 733 AFLP markers and, when identical primer combinations were used, 131 comigrating AFLP markers were identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(57 citation statements)
references
References 26 publications
1
53
0
3
Order By: Relevance
“…In the same study, it has been reported that the AFLP technique is suitable at the intraspecific level, while the interspecific phylogenies might be less reliable due to an increasing chance of the co-migration of non-homologous DNA fragments. Recent results using AFLP markers to align genetic maps from different potato genotypes (Rouppe van der Voort et al 1997), and to study Hordeum taxa (El Rabey et al 2002), proved that co-migration of bands defines similarity due to ancestry also at an interspecific level. In this study the combined use of morphological and AFLP data made possible: (1) the establishment of a genetic distance between accessions; (2) the reclassification of several taxa that were previously misidentified; (3) the new classification of eight out of nine Solanum sp.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, it has been reported that the AFLP technique is suitable at the intraspecific level, while the interspecific phylogenies might be less reliable due to an increasing chance of the co-migration of non-homologous DNA fragments. Recent results using AFLP markers to align genetic maps from different potato genotypes (Rouppe van der Voort et al 1997), and to study Hordeum taxa (El Rabey et al 2002), proved that co-migration of bands defines similarity due to ancestry also at an interspecific level. In this study the combined use of morphological and AFLP data made possible: (1) the establishment of a genetic distance between accessions; (2) the reclassification of several taxa that were previously misidentified; (3) the new classification of eight out of nine Solanum sp.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the transferability of AFLP markers is limited to the same plant species. However, even if common AFLP markers can be identiWed among populations (Qi and Lindhout 1997) and used to align genetic maps (Rouppe van der Voort et al 1997), the transferability of AFLP markers among laboratories remains disputable. We took as criteria for the selection of potentially common AFLP markers across populations the co-migration of ampliWcation products obtained with identical primer combinations and the localisation of markers to similar map positions.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-based markers, such as RAPD (Williams et al 1990), AFLP (Vos et al 1995) and IMA (Zietkiewicz et al 1994), are easy to handle and can generate more than a thousand markers in a few months. RAPDs and AFLPs were successfully used for the quick development of genetic maps in several species like Arabidopsis with RAPD markers (Reiter et al 1992), barley (Qi et al 1998), and rice (Maheswaran et al 1997;Nandi et al 1997), loblolly pine (Remington et al 1999), potato (Rouppe van der Voort et al 1998b), eucalyptus (Marques et al 1998) and melon (Wang et al 1997) with AFLP markers. IMA enables amplification of genomic DNA between adjacent inversely oriented simple-sequence repeats as revealed on an agarose or acrylamide gel (Zietkiewicz et al 1994).…”
Section: Introductionmentioning
confidence: 99%